2007
DOI: 10.1177/0969733007075888
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Self-Determination By Older Persons Living in Sheltered Housing

Abstract: Respect for autonomy and self-determination is a central principle in nursing ethics. Autonomy and quality of life are strongly connected, and, at the same time, autonomy is an important quality indicator on how older persons' housing functions. In this study, autonomy was conceived as self-determination. The aim of the study was to describe how older people living in sheltered housing experience self-determination and how they are valued as human beings. Eleven persons living in five different housing facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 10 publications
1
116
0
1
Order By: Relevance
“…Home care assistance and technological devises (such as panic buttons) can also reduce injuries and other risks to enable older persons to age in place and retain independence for longer (Simpson, 2010). This is because relocating to a care home can bring about feelings of disempowerment as independence is lost through have to adhere to new routines, decisions with consultations and negative attitudes of care home staff (Cheng, Rosenberg, Wang, Yang, & Li, 2011;Hellstrom & Sarvimaki, 2007).…”
Section: An Interconnected Physical and Social Environmentmentioning
confidence: 98%
“…Home care assistance and technological devises (such as panic buttons) can also reduce injuries and other risks to enable older persons to age in place and retain independence for longer (Simpson, 2010). This is because relocating to a care home can bring about feelings of disempowerment as independence is lost through have to adhere to new routines, decisions with consultations and negative attitudes of care home staff (Cheng, Rosenberg, Wang, Yang, & Li, 2011;Hellstrom & Sarvimaki, 2007).…”
Section: An Interconnected Physical and Social Environmentmentioning
confidence: 98%
“…This has been demonstrated earlier (Landi, et al, 2004;Condelius, et al, 2010) and the reason may be that those dependent in IADL are still capable of contacting and seeking medical healthcare, but when the dependency increases and also includes PADL they have more difficulties actually doing so. Another reason may be that those dependent in PADL have more formal help and therefore both less self-determination (Hellstrom & Sarvimaki, 2007) and a loss of power (Kristensson, et al, 2010) with the staff possibly having a moderating effect on healthcare utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The need for moving to a nursing home for support can be experienced as dependence [5-8], and along with the loss of physical function can lead to loss of autonomy [9], affecting dignity [6,7,9] and reducing freedom [10]. Bergland och Kirkevold [11] found that relationships with other older persons at nursing homes were an opportunity to have thriving experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Hasson and Arnetz [19] reveal that older persons only receive good care in nursing homes when it came to their basic needs, and Hellström and Sarvimäki [8] and Harnett [20] found that the environment does not enhance individual autonomy. Harnett also found that staff used routines as power to control older persons and did not listen to their opinions [20], which can result in impersonal care [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation